Quinolizidine alkaloid biosynthesis: recent advances and future prospects - Bunsupa, Somnuk; Yamazaki, Mami; Saito, Kazuki (Frontiers in Plant Science, 2012)
Lys-derived alkaloids, including piperidine, quinolizidine, indolizidine, and lycopodium alkaloids, are widely distributed throughout the plant kingdom. Several of these alkaloids have beneficial properties for humans and have been used in medicine. However, the molecular mechanisms underlying the biosynthesis of these alkaloids are not well understood. In the present article, we discuss recent advances in our understanding of Lys-derived alkaloids, especially the biochemistry, molecular biology, and biotechnology of quinolizidine alkaloid (QA) biosynthesis. We have also highlighted Lys decarboxylase (LDC), the enzyme that catalyzes the first committed step of QA biosynthesis and answers a longstanding question about the molecular entity of LDC activity in plants. Further prospects using current advanced technologies, such as next-generation sequencing, in medicinal plants have also been discussed.